PEM fuel cells for energy production in solar hydrogen systems - Kalogirou, Soteris A.; Panayiotou, Gregoris (My University, 2010)
The main barrier for the widespread use of Renewable Energy Sources (RES) systems is their variability and dependence on environmental conditions. Due to this problem the aspect of energy storage becomes more and more important and the prospect of using hydrogen as an energy carrier in order to store energy is becoming more attractive. This can be achieved by using a solar hydrogen energy system (SoHyS) where the electricity produced by the PVs is stored in the form of hydrogen and can be recovered on demand by using a fuel cell. One of the most promising types of fuel cells to be used in such systems is that of Proton Exchange Membrane (PEM) fuel cells due to their numerous advantages such as high efficiency, low emissions, low operating temperature, low noise levels and high energy density. In this work a brief description of PEM fuel cells and their characteristics is presented along with recent patents on some of their main research areas. The future trends of research in this area would be on improving the design for more advanced fuel cell systems so as to compensate some of the most important aspects such as structural integrity, sealing and hydration level
Keywords: Fuel cells; Proton exchange membrane fuel cells; Solar energy; Design; Hydrogen